Gambaran Kepatuhan Pelaksanaan Protokol Kesehatan Pencegahan COVID-19 pada Masyarakat Pasca Vaksinasi - Ayuniati, Ni Luh Ketut; Dewi, Ni Luh Putu Thrisna; Pramesti, Theresia Anita (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2022)
Introduction: Corona Virus Disease-19 (COVID-19) has experienced an increase in the number of cases in the world and in Indonesia in particular. Vaccination efforts are carried out by the government to reduce the transmission of COVID-19 transmission, reduce morbidity and death rates and achieve herd immunity. The problem in the field is that people who have been vaccinated have begun to neglect the implementation of health protocols. Limited study explored compliance to implement COVID-19 health protocols post vaccination. The purpose of this study was to determine the description of compliance with the implementation of the COVID-19 preventive health protocol in the post-vaccination community in the Unit Pelaksana Teknis Daerah (UPTD) work area of Rumah Sakit Umum (RSU) Payangan. Methods: the research method was descriptive research. The research sample were 268 people who had met the criteria of completed vaccinated, be able to use Whatsapp and aged 20-70 years old with the Simple Random Sampling sample technique. Data was collected with questionnaires, namely questionnaires to identify the characteristics of respondents and questionnaires to assess community compliance with implementing COVID-19 prevention health protocols and analysed by statistical test. Results: the results were obtained from 268 respondents, most of the people were obedient in using masks (83.2%), obediently washing hands (93.3%), obedient in maintaining distance (60.4%) and obedient in maintaining health (83, 2%). Conclusion: compliance in maintaining distance is the lowest compliance, the number of traditional and cultural activities in the community, economic demands and fulfilment of needs causes people to gather. It is very important to increase public supervision in implementing Health protocols and providing facilities and facilities.